Modelling of shear in post-tensioned brickwork cantilever fin walls - Shafii, Faridah (Fakulti Kejuruteraan Awam, 1995)
This paper describes a model scale investigation of the shear behaviour of post-tensioned brickwork cantilever fin walls. The developments of models to represent the critical region under shear are described. Details of reduced height test walls to simulate the actual forces and critical shear zone are presented. It is concluded that the shear behaviour of prestressed walls can be studied by modelling at reduced scale